KEPEMIMPINAN PEREMPUAN DALAM ISLAM DAN MELAYU - Akbarizan Akbarizan (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2012)
Islam is with a set of point that be taken in tries to do one process "Revolution "to human view about women at world. Gently ala but must, Syari 'at Islam begins to lift woman kind of continuous discriminatory wallow at Arabic society. woman in monographic Islami in fact reputed have then•rights with man clan. having poised the right and obligation good deep spritual’s state, moral, right for economic rights and right for rights legal in jurisdictional view